Targeting the Hedgehog Pathway for Locally Advanced and Metastatic Basal Cell Carcinoma - T. Yin, Vivian; Esmaeli, Bita (Current Pharmaceutical Design, 2017)
Basal cell caricnoma (BCC), the most common periocular magliancy, is treated with complete surgical excision. However, in patients not amenable to surgery or when surgical resection means loss of vital organs or disfiguring procedures due to locally advanced or metastatic disease, targeting the hedgehog pathway offers a novel treatment approach for such patients. Mutation in PTCH1 and SMO has been identified in patients with basal cell nevoid syndrome as well as in patients with sporadic BCC. Inhibition of SMO by vismodegib or sonidegib, the two sonic hedgehog inhibitor drugs approved by the Food and Drug Administration in the United States, has shown overall response rate for locally advanced and metastatic BCC around 50%. The most common side effects were muscle cramps, weight loss, fatigue, and lost appetite. Resistance to vismodegib has been attributed to mutation in SMO or activation of RAS/MAPK pathway. New research into dual inhibition aims to overcome this resistance and provide more lasting response.
Keywords: locally advanced BCC